Missense variant in UBA2 associated with aplasia cutis congenita, duane anomaly, hip dysplasia and other anomalies: A possible new disorder involving the SUMOylation pathway. Issue 3 (22nd January 2017) - Marble, Michael; Guillen Sacoto, Maria J.; Chikarmane, Rashmi; Gargiulo, Dominic; Juusola, Jane
Abstract : We report a patient with aplasia cutis congenita, Duane anomaly, hip dysplasia, and other anomalies who had a de novo missense variant in UBA2, which encodes for a protein involved in the SUMOylation pathway. It has previously been suggested that UBA2 haploinsufficiency underlies scalp defects in the 19q13.11 deletion syndrome. We propose that disturbance of the SUMOylation pathway, mediated by pathogenic variants in UBA2, is a novel mechanism for aplasia cutis congenita and other phenotypic abnormalities. © 2017 Wiley Periodicals, Inc.